Conversion of Cellulose to 5-HMF in the Presence of Silica-Alumina Catalysts Synthesized by Dual Template at Low Temperature - Halit Levent Hoşgün; Berrin Bozan; Emir Zafer Hoşgün; Özlem Topçu (Sakarya Üniversitesi Fen Bilimleri Enstitüsü Dergisi, 2023)
In this study, which incorporates many principles of green chemistry (use of renewable feedstocks, catalysis, improvement of energy efficiency, and harmless solvents and auxiliaries), the single-phase catalytic conversion of cellulose to 5-HMF in over silica-alumina catalysts was investigated. A series of dual-template silica-alumina catalysts with CTAB as the main template and F127 or triethylamine (TEA) as the co-template were synthesized at a low temperature of 60 °C and characterized by XRD, N2 adsorption-desorption technique, FT-IR and pyridine adsorption FT-IR. The surface area is increased by using the second template in silica-alumina catalyst. In addition, the acidity of the surface was changed by using the second template. The cellulose conversion and yield of 5-HMF increased from 36% to 52% and from 3.13% to 4.24%, respectively, due to the properties gained by using the second template. 52% cellulose conversion and 8.13% selectivity of 5-HMF were obtained in aqueous medium, 220 °C and 6 h reaction time with the catalyst using TEA as co-template. Eco-friendly silica catalysts synthesized at low temperatures with a dual template can be considered as a potential alternative for the conversion of cellulose into value-added biobased products.